Populasi dan Distribusi Ungko (Hylobates agilis) di Taman Nasional Batang Gadis, Sumatera Utara - Keni Sultan; Sri Supraptini Mansjoer; M. Bismark (Jurnal Primatologi Indonesia, 2009)
The agile gibbons (Hylobates agilis) was considered as endangered species. The information on population status of the agile gibbons are limited and fluctuative. The overall aim of this project was to generate critical baseline data on the status of agile gibbon and its distribution at Batang Gadis National Park, North Sumatera. The survey had been conducted at three different locations during August 2006 up to January 2007. Locations of the research were based on types of forests: undisturbed (primary forest) and disturbed forest (logged-over forest and post-cultivated forest). Population density of agile gibbons were conducted by fixed-point count and line transect method. The average population density for agile gibbons at post-cultivated forest was 15.5 individuals/km2, logged-over forest was 13.2 individu/km2 and primary forest was 9.9 individu/km2. While, group density for agile gibbon at post-cultivated forest was estimated at 4.7 group/km2, logged-over forest was 4.0 group/km2 dan lower at primary forest was 3.3 group/km2. There were 3,292 groups and 10,620 individuals in Batang Gadis National Park. On location research Aek Nangali Village, agile gibbons were found at 600-955 m asl but based on preliminary research on July-August 2005, agile gibbon was found at 300-1.200 m asl from north to south of  Batang Gadis National Park.    Keywords: Hylobates agilis, Batang Gadis National Park, population density dan group density